Tahap kompentensi dan masalah Penolong Kanan Kokurikulum dalam pengurusan kokurikulum di sekolah-sekolah Daerah Asajaya, Samarahan, Sarawak - Zulkeplee @ Ibrahim, Meni (2010)
The main purpose of the study is to identify the level of competency among senior cocurricular assistants and their levels of problems in managing cocurricular activities. Research samples consisted of 30 senior cocurricular assistants and 300 cocurricular teachers in primary school of Asajaya's District, Samarahan Division, Sarawaic Data on the competency level of senior awistants and their level of cocurricular management problems were collected through two perceptions (a) perceptions from senior cocurricular assistants, and (b) perception from cocurricular teachers. Cocurricular management problems were tackled based on the principles of management, which are planning, directing, controlling and evaluating. Questionnaire using Likert scale was used as a survey method to collect and analysis the data. Pilot study conducted in this research showed high reliability. SPSS 16.0 software used to analyze data and translated to be understood and thus implemented wisely and properly. Data were analyzed using descriptive (mean, standard deviation, ranking, frequency, and percentage) and inferential statistical tests (t-test, ANOVA one tailed, and Correlation Pearson Test). This study showed that senior cocurricular assistants demonstrated high competency level. The level of cocurricular management problems faced by senior cocurricular assistants were low from the points of view of both senior d c u l a r assistants and cocurricular teachers. Overall results of this study indicate that the Senior Assistant Cocurriculum has a high level of competency and level of problem management practices Senior Assistant Co-curriculum is at the level of medium and low according to the perception Senior Assistant Co-Curricular and co-curricular teachers. All theories, concepts and plans in this study is expected and recommended that it be adopted by those concerned to plan a change of mind to elevate educational visionary of education